Issues in the Home Delivery Model in India - JEHANGIR Pheroze BHARUCHA (International Journal of Supply Chain Management, 2017)
India is a perfect place where a well developed online economy would be built. Today, home delivery is increasingly becoming a key element in e-commerce. This paper has as its basis a market survey conducted for 220 respondents based in metropolitan cities of India. It is observed that home delivery operations already face significant challenges a lot of operational issues come up. These orders are delivered through smaller and more economical carriers Difficulty of returning an item and cost of delivery are major factors for the respondents not opting for home delivery services. Unavailability of respondents at the time of delivery is another major factor. There is a high first time delivery failure which increases costs for carriers and also lowers consumer satisfaction. The return rate becomes abnormally high. Home deliveries that are damaged or faulty cause significant costs to supply chain partners. The paper concludes that home delivery is a fairly new phenomenon in India. Those e-commerce companies would probably succeed more which are localised operate on a small scale with a big margin. Highly aggressive promotional campaigns would unnecessarily swell costs and not yield enough returns so word of mouth publicity would be the safest bet. Thus new models and algorithms need to be proposed and studied.